Prediction of Small-Strain Dynamic Properties on Granulated Spherical Glass Bead-Polyurethane Mixtures - Gyeong-o Kang; Woong Choi; Changho Lee (Advances in Civil Engineering)
This paper aims to propose predictive equations for the small-strain shear modulus (Gmax) and small-strain damping ratio (Dmin) of a granulated mixture with plastic and nonplastic materials to reduce the dynamic energy of the ground. Polyurethane bead (PB) and glass bead (GB) were used as the plastic and nonplastic materials, respectively. 180 resonant-column tests were conducted with various conditions affecting the dynamic properties, such as nonplastic particle content (PC), void ratio (e), particle-size ratio (sr), and mean effective confining pressure (σm′). The results showed that Gmax and Dmin, respectively, increased and decreased as e decreased with increasing σm′ of material mixtures. In addition, Gmax decreased with an increase in PC, whereas Dmin increased. It was also found that sr of materials affected the changes in Gmax and Dmin. With an increase in sr, Gmax increased while Dmin decreased because small particles do not hinder the behavior of large particles as the size of larger particles increases. Finally, based on the results, new equations for estimating Gmax and Dmin of a granulated mixture with PB and GB were proposed as functions of PC, e, median grain size (D50), and σm′.